2014
DOI: 10.1111/jcpe.12244
|View full text |Cite
|
Sign up to set email alerts
|

Platform switch versus platform match in the posterior mandible – 1‐year results of a multicentre randomized clinical trial

Abstract: ObjectiveThe purpose of this ongoing randomized study was to assess differences in bone level changes and success rates using implants supporting single crowns in the posterior mandible either with platform matched or platform switched abutments.Material and MethodsPatients aged 18 and above, missing at least two teeth in the posterior mandible and with a natural tooth mesial to the most proximal implant site were enrolled. Randomization followed implant placement. Definitive restorations were placed after a m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
55
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 42 publications
(65 citation statements)
references
References 23 publications
(38 reference statements)
9
55
0
1
Order By: Relevance
“…The finding that the marginal bone level is better preserved during healing after implant placement at implants with a PS implant/abutment connection than at implants with a PM connection is in agreement with previous animal and human studies (Baffone et al, ; Guerra et al, ; Rocha et al, ; Telleman et al, ; Weng, Nagata, Bosco, & Melo, ). Baffone et al () evaluated the effect of a mismatch between abutment and implant platform diameter in an experiment on six Labrador dogs.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The finding that the marginal bone level is better preserved during healing after implant placement at implants with a PS implant/abutment connection than at implants with a PM connection is in agreement with previous animal and human studies (Baffone et al, ; Guerra et al, ; Rocha et al, ; Telleman et al, ; Weng, Nagata, Bosco, & Melo, ). Baffone et al () evaluated the effect of a mismatch between abutment and implant platform diameter in an experiment on six Labrador dogs.…”
Section: Discussionsupporting
confidence: 91%
“…The crestal bone level was identified in a significantly more coronal position at PS‐implants than at PM‐implants 3 months after implant placement. Guerra et al (), in a RCT used radiographs to assess crestal bone level changes during 12 months postloading at 74 single implants with a PS‐design and 72 implants with a PM‐design using implants from the CAMLOG system. They reported a small bone gain or no bone loss for 67.1% of the sites with PS implants as compared to 49.2% for the implants with PM design.…”
Section: Discussionmentioning
confidence: 99%
“…2014, Messias et al. 2013) before surgery, immediately after surgery with healing abutment, at restoration placement, and every 12 months post‐loading until the 60th month appointment (Fig.…”
Section: Methodsmentioning
confidence: 99%
“…Recently, a prospective randomized‐controlled clinical multicenter trial reported positive results supporting the PS concept in commercially available implants with identical outer geometry and internal implant–abutment connection for both groups complied with the elimination of relevant confounders (Guerra et al. ). The present prospective observational study has been planned to evaluate the marginal bone level changes in implants with internal conical connection and platform switch design in the posterior mandible.…”
mentioning
confidence: 99%